Le verre : science et technologie - Barton, James; Guillemet, C. (Claude), 1931- (Les Ulis, France : EDP Sciences, 2005)
This book is a compendium of Mat Hillert's publications. Mat Hillert is a world specialist in metal alloy at the origin of a universal computing code used to calculate the diagrams of phase. This work is in English.
Annexe 6 : Fracture du verreAnnexe 7 : Statistique de Weibull; Annexe 8 : Propagation de lumière cohérente dans les fibres optiques : éléments théoriques; Annexe 9 : Données économiques; Index; Dans la même collection.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Glass; Glass -- Mechanical properties; Glass -- Optical properties; Glass -- Transport properties; Glass manufacture; Verre; Verre -- Propriétés mécaniques.; Verre -- Propriétés optiques; Verre -- Propriétés de transport; Verre -- Fabrication; glass (material); TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Glass; Glass manufacture; Glass -- Mechanical properties; Glass -- Optical properties; Glass -- Chemistry of materials; Electronic book